Obstruction of Applying E-Business among Batik Entrepreneurs in Pasar Siti Khadijah - Z. N. Raihani; K. N. Fadhilah; Yohan Kurniawan; Wan Yusoff Wan Shaharuddin (2016)
The research findings were based on the responses obtained from batik entrepreneurs in Pasar Siti Khadijah Kota Bharu, Kelantan. This paper presents a study regarding to obstruction in applying e-business among batik entrepreneurs in Pasar Siti Khadijah. There are three types of factors which are level of education, cost incurred and entrepreneurs’’ mind-set that influence the application of e-business. A total of 31 batik entrepreneurs in Pasar Siti Khadijah participated in this study. Data was collected through self-administered questionnaires that have been distributed to the respondents. This study is important for the entrepreneurs to increase the variety of method in marketing, at the same time; boost the economy of Batik industries. Data obtained was analysed using correlation Analysis. The results have shown that the factors influencing the obstruction of e-business application. It is hoped that this research will help students, lecturers, job seekers, entrepreneur and the government in understanding the importance of e-business. The limitation of this study was the sample size, time management, and cooperation from respondents, which was not sufficient.